2012
DOI: 10.1248/cpb.60.536
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Diffusivity of Water Molecules Inside Hydrating Tablets and Their Drug Release Behavior Elucidated by Magnetic Resonance Imaging

Abstract: We reported previously that sustained release matrix tablets showed zero-order drug release without being affected by pH change. To understand drug release mechanisms more fully, we monitored the swelling and erosion of hydrating tablets using magnetic resonance imaging (MRI). Three different types of tablets comprised of polyion complex-forming materials and a hydroxypropyl methylcellulose (HPMC) were used. Proton density-and diffusion-weighted images of the hydrating tablets were acquired at intervals. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…13 The progress of water penetration and the water mass content into the hydrated gel can be evaluated by gravimetric technique, or by more complex techniques such as the use of texture analyzer 12 or MRI. 14 Each technique offers its own advantages which suit different study purposes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 The progress of water penetration and the water mass content into the hydrated gel can be evaluated by gravimetric technique, or by more complex techniques such as the use of texture analyzer 12 or MRI. 14 Each technique offers its own advantages which suit different study purposes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The ADC maps and T 1 maps of purified water were acquired, followed by the random sampling of the MR parameters from the maps. The mean values of T 1 and ADC were 2.98 ± 0.19 s and 21.2 ± 0.8 × 10 −10 m 2 /s, respectively; these values are comparable to those of pure water . A statistical analysis of the data revealed that although there was no significant difference between PBS and purified water in terms of ADC, the T 1 values of PBS were significantly shorter than were those of purified water ( p < 0.001) (data not shown).…”
Section: Resultsmentioning
confidence: 75%
“…Our MRI method enables the detection of the change in the emulsion state by the visualization of the difference in the state of water. We note that the sensitivity of the detection limit of our method is superior to that of visual observations; e.g., slight creaming, which is not visible to the naked eye, can be visualized clearly. , To date, in addition to the emulsion stability, we have applied the MRI technique to various pharmaceutical properties including the state of water in a gel formulation and the swelling properties of tablets …”
Section: Introductionmentioning
confidence: 94%
“…15,16 To date, in addition to the emulsion stability, we have applied the MRI technique to various pharmaceutical properties including the state of water in a gel formulation 20 and the swelling properties of tablets. 21 We assumed that our MRI method allows us to visualize the dispersion state of NPs by distinguishing the restricted solvent from the bulk solvent. There are several technical reports that support our expectation.…”
Section: ■ Introductionmentioning
confidence: 99%